Synergistic antibacterial effect of inhaled aztreonam and tobramycin fixed dose combination to combat multidrug-resistant Gram-negative bacteria - Wang, J.; Kutter, J.P.; Mu, H.; Moodley, Arshnee; Yang, M. (Elsevier, 2020)
The limited therapeutic option for respiratory infections caused by multi-drug resistant microbial pathogens is a major global health threat. Topical delivery of antibacterial combinations to the lung could dramatically enhance antibacterial activities and provide a means to overcome bacterial resistance development. The aim of the study was to investigate the potential of new inhalable dry powder combinations consisting of a fixed dose of aztreonam (Azt) and tobramycin (Tob) using a spray drying process, against antibiotic resistant Gram-negative respiratory pathogens. The interactions of Azt with Tob on resistant Pseudomonas aeruginosa, Klebsiella pneumoniae and Acinetobacter baumannii were determined by calculating factional inhibitory concentration indices (FICI). A fixed concentration ratio of Azt and Tob that exhibited a synergistic antimicrobial effect was selected and formulated into inhalable dry powders by co-spray drying with and without L-leucine. The obtained dry powders were characterized with respect to the morphology, particle size distribution, solid state, moisture sorption behaviour, and in vitro dissolution. Storage stability, aerosol performance, and in vitro antibacterial activity were also evaluated. Inhalable dry powders consisting of Azt, Tob and L-leucine could be readily obtained via the spray drying process with a fine particle fraction of above 40% as determined using a next generation impactor. The co-spray drying process resulted in amorphous Azt/Tob dry powders with or without the addition of L-leucine as indicated by X-ray powder diffraction. The dissolution rates of the co-spray dried Azt/Tob dry powders were decreased, and the storage stability was improved with an increase in the proportion of L-leucine in the formulations. The inclusion of L-leucine did not affect the minimum inhibitory concentration and the co-spray dried powders reserved the synergistic antibacterial effects and exhibited enhanced antibacterial activities as compared to the individual antibiotic used alone on multidrug-resistant (Azt and Tob resistant) P. aeruginosa 25756 and A. baumannii K31. This study demonstrates that inhalable Azt/Tob dry powders using L-leucine as a moisture protector as well as a dispersing agent can be readily prepared by the spray drying process. This new inhalable fixed dose combinational dry powders may represent an alternative treatment against multidrug-resistant Gram-negative respiratory pathogens.